RAC1 as a Therapeutic Target in Malignant Melanoma - Cannon, Alexa (Trends Cancer, 2020)
Small GTPases of the RAS and RHO families are related signaling proteins that, when activated by growth factors or by mutation, drive oncogenic processes. While activating mutations in KRAS, NRAS, and HRAS genes have long been recognized and occur in many kinds of cancers, similar mutations in RHO family genes such as RAC1 and RHOA have only recently been detected as the result of extensive cancer genome sequencing efforts and are linked to a restricted set of malignancies. In this review, we focus on the role of RAC1 signaling in malignant melanoma, emphasizing recent advances that describe how this oncoprotein alters melanocyte proliferation and motility and how these findings might lead to new therapeutics in RAC1-mutant tumors.